Effect of nitrogen application rate on yield, forage quality, and animal performance in a tropical pasture - Delevatti, Lutti M. [UNESP]; Cardoso, Abmael S. [UNESP]; Barbero, Rondineli P.; Leite, Rhaony G. [UNESP]; Romanzini, Eliéder P. [UNESP]; Ruggieri, Ana C. [UNESP]; Reis, Ricardo A. [UNESP] (Springer Nature, 2019)
A three-year-long field experiment was conducted in a continuous grazing system with a variable stocking rate to evaluate effects of increasing nitrogen levels in Marandu grass (Brachiaria brizantha Hochst ex A. Rich Stapf “marandu”) on herbage mass, forage accumulation rate (FAR), forage quality, stocking rate (SR), average daily gain (ADG), gain per hectare (GPH), and gain per kg of applied N. The experimental design was completely randomized with four treatments (control without application of N, and 90, 180, and 270 kg N ha −1 year −1 ) and three replicates (paddocks per treatment); nitrogen was applied in the form of urea. Herbage mass, crude protein (CP), FAR, SR, GPH, and the nitrogen nutrition index increased with increasing nitrogen level (P < 0.05), whereas the neutral detergent fibre (NDF), acid detergent fibre, and nitrogen usage efficiency decreased with increasing nitrogen level (P < 0.01). Crude protein was higher than 12% and NDF lower than 60% in all treatments. Nitrogen application rate affected ADG (P < 0.05) but did not fit any equation. The highest ADG was 90 kg N ha −1 year −1 (985 g animal −1 day −1 ). Increasing the nitrogen level is a promising way to improve Marandu grass production, nutritive value, and animal production.